Social relationships and their impact on health-related outcomes in peritoneal versus haemodialysis patients: a prospective cohort study. Issue 7 (23rd January 2018) - Neumann, Denise; Lamprecht, Juliane; Robinski, Maxi; Mau, Wilfried; Girndt, Matthias
ABSTRACT: Background: Social relationships are important determinants of health-related outcomes for patients with chronic conditions. However, the effects of social networks and social support on health outcomes of dialysis patients in different treatment modalities have been under studied. Methods: We surveyed peritoneal dialysis (PD) and haemodialysis (HD) patients in the Choice of Renal Replacement Therapy project about their social relationships and health-care outcomes at baseline and 1-year follow-up. Two propensity score-matched groups ( n = 353; HD = 200, PD = 153) with similar age, comorbidity level, education and employment status were compared. We used an ego-centred Network Generator to assess quantitative and qualitative aspects of social networks and the Berlin Social Support Scales to evaluate dimensions of social support, and analysed the effects of the social variables on anxiety, depression, autonomy preferences, and physical and psychological quality of life. Results: Over time, the non-family networks (e.g. friends) of both groups decreased (P = 0.04) and the absolute number of types of relationships increased (P = 0.01). The family-network size, quality of relationships and social support remained stable. Larger social networks were associated with higher participation-seeking preferences ( B = 1.39, P = 0.002) and lower anxiety ( B = −0.11, P = 0.03). Closer and more satisfying relationships were associated with better psychological well-being ( B = 3.41, P = 0.003). PD patients had larger networks, more types of relationships and received more social support than HD patients (P ≤ 0.05). Conclusions: These differences may reflect the degree of autonomy and self-care associated with the different treatment modalities. In practice, our findings suggest that the early identification and inclusion of persons providing social support for patients may have a positive effect on different aspects of their care and quality of life.